Pengaruh Opinion Shopping, Debt Default, dan Prior Opinion terhadap Penerimaan Opini Audit Going Concern - Ayu Lestari; Pupung Purnamasari; Mey Maemunah (UNISBA Press, 2022)
Abstract. This study aims to determine the effect of opinion shopping, debt default, and prior opinion on going concern audit opinion acceptance. The research method used in this study is a descriptive verification method with a quantitative approach. This study uses secondary data with a sample of 27 mining sector companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period with a total of 81 observational data. Hypothesis testing in this study uses logistic regression analysis with SPSS 23 statistical tools. The test results show that opinion shopping has a significant effect in a positive direction on the acceptance of going-concern audit opinion, debt default has no effect on the acceptance of going-concern audit opinion, and prior opinion has a significant effect on the acceptance of going-concern audit opinion. positive direction towards the acceptance of going concern audit opinion. Suggestions for further research to be able to use other units of analysis and add or replace independent variables that are not explained in this study related to the acceptance of going-concern audit opinions. Abstrak. Penelitian ini bertujuan untuk mengetahui pengaruh opinion shopping, debt default, dan prior opinion terhadap penerimaan opini audit going concern. Metode penelitian yang digunakan pada penelitian ini adalah metode deskriptif verifikatif dengan pendekatan kuantitatif. Penelitian ini menggunakan data sekunder dengan sampel sebanyak 27 perusahaan sektor pertambangan yang terdaftar di Bursa Efek Indonesia (BEI) periode 2017-2019 dengan total 81 data pengamatan. Pengujian hipotesis pada penelitian ini menggunakan analisis regresi logistik dengan alat statistik SPSS 23. Hasil pengujian menunjukkan bahwa opinion shopping berpengaruh signifikan dengan arah positif terhadap penerimaan opini audit going concern, debt default tidak berpengaruh terhadap penerimaan opini audit going concern, dan prior opinion berpengaruh signifikan dengan arah positif terhadap penerimaan opini audit going concern. Saran bagi penelitian selanjutnya untuk dapat menggunakan unit analisis lain dan menambah atau mengganti variabel independen yang tidak dijelaskan pada penelitian ini terkait penerimaan opini audit going concern.